Structure and Composition Seedling Plant in the Campus Forest of UIN Sulthan Thaha Saifuddin Jambi - Nurfadillah, Nurfadillah; Susanti, Try; Manurung, Aini Qomariah; Riany, Hesti (Universitas Labuhanbatu, 2023)
Seedlings are the first stands that grow to replace damaged forest vegetation. Seedlings can have a positive impact on the balance of the wider ecosystem, because seedlings are the beginning of an ecosystem regeneration process that is greatly influenced byÂ thatÂ ecosystem The purpose of this research to information regarding the structure and composition of seedling in the UIN Sulthan Thaha Saifuddin Jambi Campus Forest. This research was carried out in July 2022 â€“ March 2023. The research location was determined using the Purposive Sampling Method, determining the plot using systematic sampling, and data collection using the quadratic method with a size of 2 m x 2 m. The observation results were analyzed using the Importance Value Index, Shannon-Winner Diversity Index, Morisita Index, and the Evenness Index. The research results found that there were 332 individuals, 84 types of seedlings, belonging to 28 families. The highest Importance Value Index (INP) is Gmelina arborea Roxb (11.19%), the Diversity Index (H') is in the high category (H' 3.94). The evenness index (E) (0.89) is in the high (even) category.